Meningkatkan Hasil Belajar Peserta Didik Pada Materi Ipa Dengan Menggunakan Metode Course Riview Horay Di Kelas V Sd Negeri 04 Mowila Kabupaten Konawe Selatan - Ni Nyoman Ayu Trisnawati; Ashari Usman; La Sisi (Prodi PGSD Unsultra, 2021)
This study aims to improve students’ learning outcomes in science subjects using the Course Review Horay method in Grade V of Elementary School 04 Mowila. This type of research is Classroom Action Research (CAR). The subjects in this study were 20 fifth-grade students. The improvement in students’ learning outcomes was observed through two cycles. In the first cycle, there were 8 students who did not reach the mastery level with a success rate of 40%, and 12 students achieved mastery with a percentage of 60%. In the second cycle, only 2 students did not reach the mastery level (10%), while 18 students achieved mastery, reaching a 90% success rate. These results indicate that the use of the Course Review Horay method can effectively improve students’ learning outcomes in science learning